2015
DOI: 10.1161/circinterventions.114.001781
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intracoronary Versus Intravenous Administration of Adenosine for Measurement of Coronary Fractional Flow Reserve

Abstract: Background-Measurement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 37 publications
4
51
1
Order By: Relevance
“…The phenomenon reported in our study highlights the possibility of false low FFR values with overestimation of hemodynamic significance when automatic FFR detection occurs during the induction phase of hyperemia. Correspondingly, detailed analysis of BlandAltman plots from previously published studies revealed substantial differences C0.05 to both directions in single patients [26,28,29], and the rate of classification mismatch between automatically detected and steady-state FFR in our study was comparable with rates of overestimation of functional significance after IC adenosine administration. Our results question accuracy of the concept of IC bolus injection for induction of maximum hyperemia for intracoronary pressure measurements, because identification of steady-state hyperemia is difficult if even possible.…”
Section: Classification Mismatch Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…The phenomenon reported in our study highlights the possibility of false low FFR values with overestimation of hemodynamic significance when automatic FFR detection occurs during the induction phase of hyperemia. Correspondingly, detailed analysis of BlandAltman plots from previously published studies revealed substantial differences C0.05 to both directions in single patients [26,28,29], and the rate of classification mismatch between automatically detected and steady-state FFR in our study was comparable with rates of overestimation of functional significance after IC adenosine administration. Our results question accuracy of the concept of IC bolus injection for induction of maximum hyperemia for intracoronary pressure measurements, because identification of steady-state hyperemia is difficult if even possible.…”
Section: Classification Mismatch Analysissupporting
confidence: 79%
“…Two recently published studies reported no significant differences between FFR measurements following IC injection or IV infusion of adenosine [26,27]. However, the authors did not precisely report whether they used automatically detected or true steady-state FFR, and FFR was continuously averaged during five cardiac cycles in one trial [26]. The phenomenon reported in our study highlights the possibility of false low FFR values with overestimation of hemodynamic significance when automatic FFR detection occurs during the induction phase of hyperemia.…”
Section: Classification Mismatch Analysiscontrasting
confidence: 56%
See 1 more Smart Citation
“…39,40 However, the chances of securing the same dichotomous treatment recommendation by each method of adenosine administration falls to 78 % at FFR values of approximately 0.80 41 and there is a hyperaemic dose-response relationship seen with intracoronary doses of >60 μg. 42 The route of adenosine administration differs from centre to centre, 43 and while FFR measurement with central administration of intravenous adenosine is considered the gold standard, in the era of transradial PCI, intracoronary or peripheral intravenous administration of adenosine is more practical, although this does give similar FFR results to centrally administered adenosine.…”
Section: Routes and Doses Of Adenosine Administrationmentioning
confidence: 99%
“…injection (typically at a dose of 140 lg/kg/min) or as an intracoronary (i.c.) bolus [11]. For that purpose, use of doses between 6 lg and 720 lg has been reported [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%